2003
DOI: 10.1046/j.1523-1747.2003.12510.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiol Antioxidants Block the Activation of Antigen-Presenting Cells by Contact Sensitizers

Abstract: Strong contact sensitizers are able to induce signal transduction mechanisms such as tyrosine phosphorylation and activation of MAP kinases in antigen-presenting cells. We studied the capacity of different antioxidants (ascorbic acid, alpha-tocopherol, pyrrolidine dithiocarbamate, N-acetylcysteine, and glutathione) to block the increase in tyrosine phosphorylation in human monocytes seen after stimulation with strong contact sensitizers. Human peripheral blood mononuclear cells were stimulated with 5-chloro-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…The results showed that p38 phosphorylation in DC may be useful for the identification of potential skin contact sensitisers. The activation of p38 MAPK and ERK1/2 was also induced by the sensitiser TNCB in DC (Bruchhausen et al, 2003) and MAPKs activation by contact sensitisers was later confirmed (Aiba et al, 2003). The authors stimulated human monocyte-derived dendritic cells with nickel and DNCB and observed that DNCB-induced p38 MAPK and JNK1/2 phosphorylation, whereas nickel-induced p38 MAPK, JNK1/2 and ERK1/2 phosphorylation.…”
Section: Activation Of the Mitogen-activated Protein Kinases (Mapks)mentioning
confidence: 84%
“…The results showed that p38 phosphorylation in DC may be useful for the identification of potential skin contact sensitisers. The activation of p38 MAPK and ERK1/2 was also induced by the sensitiser TNCB in DC (Bruchhausen et al, 2003) and MAPKs activation by contact sensitisers was later confirmed (Aiba et al, 2003). The authors stimulated human monocyte-derived dendritic cells with nickel and DNCB and observed that DNCB-induced p38 MAPK and JNK1/2 phosphorylation, whereas nickel-induced p38 MAPK, JNK1/2 and ERK1/2 phosphorylation.…”
Section: Activation Of the Mitogen-activated Protein Kinases (Mapks)mentioning
confidence: 84%
“…Since then, many studies have identified signals, which can generally be divided into pathogen-associated patterns, such as LPS (49,50) and CpG oligodeoxynucleotides (51,52), and indicators of cell toxicity (27), such as uric acid release (28) or thiol depletion (30,33,53). The effect of these signaling pathways is to switch a T cell response to a specific Ag from tolerance to full activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that dendritic cell maturation signals can also be provided by necrotic cell death through the release of intracellular molecules into the extracellular matrix (27,28), apoptotic cell death (29), or the induction of oxidative stress (30,31). Indeed, studies with contact sensitizers have demonstrated that small protein-reactive compounds can induce dendritic cell maturation (30,32,33) at concentrations associated with significant cell death (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, many in vitro studies have revealed that ROS production is induced by contact allergens (Bruchhausen et al, 2003;Mehrotra et al, 2005;Martin et al, 2011). In human monocytes, the inhibition of ROS production, as achieved by administration of the NADPH oxidase inhibitor diphenyleneiodonium (DPI), inhibits ATP-mediated inflammasome activation (Hewinson et al, 2008).…”
Section: Nlrp3mentioning
confidence: 99%